ASSESSMENT OF THE IMPLEMENTATION OF THE NATIONAL CRITERIA FOR COMMUNE HEALTH STATIONS IN MOC HOA DISTRICT, 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of implementation of the National Criteria for Commune Health Stations in Moc Hoa district, Long An province (formerly), in 2024.Materials and methods: A cross-sectional descriptive study was conducted from June to December 2024 at 7 commune/commune-town health stations in Mộc Hóa district. Data were collected based on 47 indicators under 10 criteria of the National Criteria for Commune Health Stations toward 2030. Data were entered using Microsoft Excel software and analyzed with SPSS version 20.0 software.Results: The average score for the implementation of the National Criteria for Commune Health Stations among the 7 health stations was 91.47 out of 100 points. Several criteria achieved high scores, including infrastructure, preventive medicine, population and family planning, and health communication and education. However, some indicators remained limited, such as insufficient health workforce according to the job position scheme, incomplete medical equipment, limited capacity to perform technical services at the commune level, and uneven application of information technology. In addition, the proportion of residents participating in health insurance in some areas did not meet the required target.Conclusion: The implementation of the National Criteria for Commune Health Stations in Mộc Hóa district, Long An province in 2024 achieved relatively good results. However, further efforts are needed to strengthen human resources, improve medical equipment, and enhance the operational capacity of commune health stations in order to improve the quality of primary health care for the population.
Keywords: Primary health care, National Criteria for Commune Health Stations, commune health stations.